The importance of social relationships in depression in autistic adolescents: a narrative-review - Mamimoué, Élise; Gauld, Christophe (Frontiers in Psychology, 2024)
Objective. The impact of social relationships on autistic adolescents has been recently studied. However, the link between social relationships and depression in autistic adolescents seem underrepresented in the scientific literature. Especially no specific assessment tool has been developed to evaluate depression in autistic adolescents. The aim of this narrative review is to raise the impact of social relationships on depression in autistic adolescents. We aim to propose lines of thought on the creation of a sensitive tool for identifying depression in this population.Methods. We conducted two types of searches for articles and reviews on PubMed, Embase, and Cochrane. First, regarding social relationships, we searched the following terms: [("adolesc*" OR "youth") AND ("ASD" OR "autis*") AND ("social communication" OR "peer relationship") AND ("depress*")].Secondly, regarding assessment tool, we searched the following terms: [("tool" OR "assess*") AND ("depress*") AND ("ASD" OR "Autis*)"].Results. Social impact, verbal skills, and good social motivation are risk factors of depression in autistic adolescents. Social impairment during childhood is related to peer victimization and is a risk factor for depression. There is no specific tool to measure depression in autistic adolescents.No specific tool based on social relationships was developed to evaluate depression in autistic adolescents. Depression in autistic adolescents needs to be assessed considering the social and pragmatic specificities of autism. Social communication and difficulties in peer relationships may be evaluated in specific assessment tools based on social relationships for depression in autistic adolescents.